Cui Bono?: Identifying patient groups that may benefit from granulocyte transfusions in pediatric hematology and oncology - Johann, Pascal-David; Wuchter, Patrick; Trojanová, Lenka; Sturm, Dominik; Lu, Kevin Hai-Ning; Kulozik, Andreas; Kunz, Joachim (Journal of pediatric hematology - oncology, 2022)
Introduction: - Granulocyte transfusions have long been used to bridge the time to neutrophil recovery in patients with neutropenia and severe infection. Recent randomized controlled trials did not prove a beneficial effect of granulocyte transfusions, but were likely underpowered and suffered from very heterogeneous study populations. - Methods: - We retrospectively reviewed data of all patients treated with granulocyte transfusions at our pediatric center from 2004 to 2019. To identify parameters that predict the success of granulocyte transfusions, we stratified patients in 3 groups. Patients in group 1 cleared their infection, whereas patients in group 2 succumbed to an infection in neutropenia despite granulocyte transfusions. A third group included all patients who died of causes that were not related to infection. - Results: - We demonstrate that patients without respiratory or cardiocirculatory insufficiency are enriched in group 1 and more likely to benefit from granulocyte transfusions than patients who already require these intensive care measures. The effect of granulocyte transfusions correlates with the cell dose per body weight applied per time. With our standard twice weekly dosing, patients with a body weight below 40 kg are more likely to achieve a sufficient leukocyte increment and clear their infection in comparison to patients with a higher body weight. - Discussion/Conclusions: - We suggest that future studies on the benefits of granulocyte transfusions stratify patients according to clinical risk factors that include the need for respiratory or cardiocirculatory support and strive for a sufficient dose density of granulocyte transfusions.